The from farm to cup speciality coffee trend in Thailand and Vietnam. A major assumption about shortening supply chains disproven? - Azavedo, Mark (Technium Social Sciences Journal, 2021)
Shortening the supply chain of speciality coffee between farm and cup has often been spoken of as an aspiration. This study aimed to discover whether that aspiration has translated into a reality in Thailand and Vietnam. If supply chains have shortened the question then became what are the benefits and dis-benefits of that and to whom? A summary of that mainly focused on farm incomes as increased, and product quality increased, but prices also increased. The Importance of the last is that it entirely contradicts classical supply chain theory that sees prices to the end consumer falling as the number of intermediaries along the supply chain reduces.